The ‘Fisika Gasing’: Enhancing Kinematics Understanding and Student Satisfaction in a Biology Education at Mataram University - Taufik, Muhammad (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
The influence of the ‘Fisika Gasing’ technique on kinematics comprehension and student satisfaction was explored in this research of 27 biology education students. The study used a post-test design and an 8-item questionnaire to assess students' understanding of important concepts after participating in the ‘Fisika Gasing’ exercises, as well as their general satisfaction with the approach. The analysis of the post-test findings demonstrated that students' kinematics understanding improved significantly, confirming the method's efficiency in fostering conceptual knowledge. Furthermore, questionnaire results demonstrated a high level of satisfaction with the ‘Fisika Gasin’, emphasizing its capacity to generate engagement, improve knowledge, and raise confidence in dealing with kinematics challenges. These findings imply that the ‘Fisika Gasing’ approach has a lot of potential as a fascinating and effective pedagogical tool for boosting kinematics learning and cultivating student happiness in biology education programs. Further study on its long-term influence and applicability in various learning contexts is urged.